The Nexus between Instructional Supervision, Supervisors’ and Teachers’: The Practical Paradox and Its Effect on Quality Education a case of Woliat Zone Administration Elementary and Secondary Schools (1-8) - Dea, Mulatu (IJRDO- Journal of Educational Research, 2016)
Even though the new instructional supervision practices materialized in the schools level, teachers were not properly supported well, so that the students achievements was decreasing in national exams than before as the regional grade report documents revealed and quality is deteriorating from time to times. Hence, the main objective of this study is explore the practice of instructional supervision and interaction of teachers and supervisors at Wolaita zone Administration elementary and secondary schools and to see the nexus between the practices and quality education. Cross sectional survey type research design were instrumental. The research approach was quantitative dominant qualitative. Questionnaire (5 Likert scale items), Key informant interview and document analysis were employed as data collection instruments. To check internal consistency reliability Cronbach’s Alpha with value of r=0.852. The schools were selected through cluster sampling technique; availability sampling for woreda supervision head and cluster supervisors’, moreover purposive sampling technique for school leaders. Simple random sampling was employed to select the teachers’. Based on this technique, a total of 229 respondents were taken and the sample size determination focuses on 95 % confidence level and within 5 % confident limit. One way ANOVA were used to see the variations between and within groups by considering its assumptions. Moreover, binary logistic regression model adopted to determine the relationship between a binary dependent variable and a set of independent variables at Beta label (β). Chisquared test were also used to see the relationship between two categorical variables. From the study it is possible to conclude that, even though the instructional supervision require cooperative work, the sample schools were not found to be working mutually and the practice also lacks regular and continuous support to teachers in the ways to improve teaching learning methods and improving students’ performance, lacks appropriate guidelines and resources and no standardized data collection instrument to collect information at the time of instructional supervision, the involvement of stakeholders were insignificant. The study also reveals statistically significant relationship between instructional supervision, supervisors and teachers relation, stakeholders involvement with quality education. Thus, to the effective practices of instructional supervision at respective schools the researcher recommended different strategic pillars.